2015
DOI: 10.1007/s13277-015-3597-6
|View full text |Cite
|
Sign up to set email alerts
|

The pleiotropic effects of fisetin and hesperetin on human acute promyelocytic leukemia cells are mediated through apoptosis, cell cycle arrest, and alterations in signaling networks

Abstract: Fisetin and hesperetin, flavonoids from various plants, have several pharmaceutical activities including antioxidative, anti-inflammatory, and anticancer effects. However, studies elucidating the role and the mechanism(s) of action of fisetin and hesperetin in acute promyelocytic leukemia are absent. In this study, we investigated the mechanism of the antiproliferative and apoptotic actions exerted by fisetin and hesperetin on human HL60 acute promyelocytic leukemia cells. The viability of HL60 cells was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…Fisetin and hesperetin induced apoptosis along with inhibited cell proliferation, induced G2/M arrest, disrupted the mitochondrial potential, and increased caspase‐3 activity. Microarray gene profiling of treated cells revealed some important biological pathways including MAPK, DNA binding signaling pathways and genes involved in cell proliferation, division, and apoptosis . Another similar study demonstrated the effect of fisetin and hesperetin combination on human K562 CML cells.…”
Section: Fisetin and Leukemiamentioning
confidence: 73%
See 1 more Smart Citation
“…Fisetin and hesperetin induced apoptosis along with inhibited cell proliferation, induced G2/M arrest, disrupted the mitochondrial potential, and increased caspase‐3 activity. Microarray gene profiling of treated cells revealed some important biological pathways including MAPK, DNA binding signaling pathways and genes involved in cell proliferation, division, and apoptosis . Another similar study demonstrated the effect of fisetin and hesperetin combination on human K562 CML cells.…”
Section: Fisetin and Leukemiamentioning
confidence: 73%
“…Combination treatment significantly modulated genes involved in cell proliferation, cell division, apoptosis, cell cycle, and various other cellular processes such as replication, transcription, and translation. Microarray gene profiling analysis revealed genes involved in JAK/STAT pathway, KIT receptor, and growth hormone receptor signaling to be potential candidates of fisetin‐hesperetin combination for targeted CML therapy .…”
Section: Fisetin and Leukemiamentioning
confidence: 99%
“…mitogen activated protein kinases (MAPK), NF-κB, JAK/STAT, PI3K/Akt, Wnt, and mTOR pathways (Adan and Baran, 2015). Genistein, the isoflavone of soybean exerts its anticancer effects via inhibition of NF-κB and Akt signaling pathways (Li et al, 2012).…”
Section: Molecular Targets and Mechanisms Of Action Of Anticancer Phymentioning
confidence: 99%
“…Likewise, in flavonoid‐treated Kasumi‐1 cells, leukemic cell line with an 8; 21 chromosome translocation, activated form of caspase 3, 9, and PARP improved meaningfully, and consequently apoptosis rate of target cells augmented noticeably (B. Wang et al, ). As well, it was shown that flavonoid, hespertin, and fisetin, increased activated form of the caspase 3 in flavonoid‐treated acute promyelocytic leukemia (APL) cells (Adan & Baran, ). In addition, flavonoids in AML cells carrying nucleophosmin 1 (NPM1) mutation‐induced apoptosis via the activation of caspase 8.…”
Section: Flavonoids Functional Mechanisms In Leukemia Cellsmentioning
confidence: 99%